Modelling and molecular docking studies of the cytoplasmic domain of Wsc-family, full-length Ras2p, and therapeutic antifungal compounds. (February 2019) - Vélez-Segarra, Vladimir; Carrasquillo-Carrión, Kelvin; Santini-González, Jorge J.; Ramos-Valerio, Yabdiel A.; Vázquez-Quiñones, Luis E.; Roche-Lima, Abiel; Rodríguez-Medina, José R.; Parés-Matos, Elsie I.
Graphical abstract: Highlights: Wsc-family is involved in protein-protein interactions with each other and with Ras2p. Motif I of the cytoplasmic tail of the Wsc-family is capable to interact more closely to Ras2p. Yeast cells were most susceptible to all compounds with the double mutant wsc2Δwsc3Δ strain. Calcofluor White preferably binds to Wsc1p, meanwhile Caspofungin binds to Wsc3p, Wsc1p and more weakly to Wsc2p. MTiOpenScreen predict new compounds with equal affinity or binding to the three cytoplasmic domains of the Wsc-family. Abstract: Saccharomyces cerevisiae, the budding yeast, must remodel initial cell shape and cell wall integrity during vegetative growth and pheromone-induced morphogenesis. The cell wall remodeling is monitored and regulated by the cell wall integrity (CWI) signaling pathway. Wsc1p, together with Wsc2p and Wsc3p, belongs to a family of highly O-glycosylated cell surface proteins that function as stress sensors of the cell wall in S. cerevisiae . These cell surface proteins have the main role of activating the CWI signaling pathway by stimulating the small G-protein Rho1p, which subsequently activates protein kinase C (Pkc1p) and a mitogen activated protein (MAP) kinase cascade that activates downstream transcription factors of stress-response genes. Wsc1p, Wsc2p, and Wsc3p possess a cytoplasmic domain where two conserved regions of the sequence have been assessed to be important for Rom2p interaction. Meanwhile, other research groups have also proposed that these transmembrane proteins could support protein-protein interactions with Ras2p. Molecular structures of the cytoplasmic domain of Wsc1p, Wsc2p and Wsc3p were generated using the standard and fully-automated ORCHESTAR procedures provided by the Sybyl-X 2.1.1 program. The tridimensional structure of full length Ras2p was also generated with Phyre2. These protein models were validated with Procheck-PDBsum and ProSA-web tools and subsequently used in docking-based modeling of protein-protein and protein-compound interfaces for extensive structural and functional characterization of their interaction. The results retrieved from STRING 10.5 suggest that the Wsc-family is involved in protein-protein interactions with each other and with Ras2p. Docking-based studies also validated the existence of protein-protein interactions mainly between Motif I (Wsc3p > Wsc1p > Wsc2p) and Ras2p, in agreement with the data provided by STRING 10.5. Additionally, it has shown that Calcofluor White preferably binds to Wsc1p (-9.5 kcal/mol), meanwhile Caspofungin binds to Wsc3p (-9.1 kcal/mol), Wsc1p (-9.1 kcal/mol) and more weakly Wsc2p (-6.9 kcal/mol). Thus, these data suggests Caspofungin as a common inhibitor for the Wsc-family. MTiOpenScreen database has provided a list of new compounds with energy scores higher than those compounds used in our docking studies, thus suggesting these new compounds have a better affinity towards the cytoplasmic domains and Ras2p. Based on these data, there are new and possibly more effective compounds that should be considered as therapeutic agents against yeast infection.